Unpacking the past: The ambivalent legacy of colleges of education (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
The positive memory of teacher education colleges within South African higher education, often leading to a call to re-open the colleges, is usually based on an argument that colleges offered more ‘practical’ teacher preparation than today’s universities. In this article we draw on a variety of historical sources and artefacts, produced for an exhibition on colleges in the Western Cape, to reflect in greater depth on the experiences of college life. We use the concept of embodied knowledge that recognises the interconnectedness of knowledge, being and feeling with context to probe the sources and discuss ways in which colleges built a sense of community. At the same time, we illustrate the ambivalent legacy of these colleges, in their racial inequalities and constrained and often alienating curricula. We conclude by suggesting principles of teacher education that continue to be relevant, even as contemporary approaches to teacher education, and current policies and conditions, preclude a return to the past.
Keywords: Colleges of Education; Embodied Knowledge; Memory; Models of Teacher Education; Teacher Education Pedagogy; eory and Practice in Teacher Education